(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Methodological base of research in given clause was made with modern concepts Islamic банкинга and Islamic model of financing takaful (insurance) as a whole. Findings: the results indicate the mathematical model consists of a probability space, a Brownian motion and a Poisson process. The jumps are independent and identically distributed. The approach consists of defining a notion of risk and production instrument takaful (insurance) in order to minimize the risk. Originality/value: - In new judgement the principle «riba» an islam breaking moral laws as an interdiction of usury and its significant advantages in any spheres of human life is shown; - The author’s financial analysis of economic experience Islamic banking in the countries of near and far abroad as new judgement of Islamic bank system is lead; - In a new context features of financial specificity Islamic model of financing takaful (insurance) in modern Kazakhstan are revealed. Keywords: Islamic Bank, financial instruments the Islamic banking, takaful (insurance), risk management.